UTILIZATION OF MOTION GRAPHICS–BASED LEARNING MEDIA TO SUPPORT INTEGRATED SCIENCE LEARNING IN INDONESIAN JUNIOR HIGH SCHOOL: LITERATURE REVIEW - Ummah, Kuntum Khaira; Sari, Monica Prima; Muttaqiin, Arief; Mardhiah, Hayatul; Dewi, Sepni Linda; Apriaminanda, Dwipo; Abdullah, Habbieb; Wahyuni, Febri (Pendidikan IPA, FMIPA, UNP, 2024)
This study aims to determine the effect of using Motion Graphic Video-based science learning media as a supporting tool for science learning in junior high schools in Indonesia. This study uses the Systematic Literature Review method through analysis of the findings on 31 scientific articles found. The search for scientific articles is carried out through the google shcolar database with a publication range of 2010 to 2021. The technique of presenting research data is presented in the form of graphs and tables. The results showed that there was an effect of using motion graphic video media on the results and learning processes of students in the science class. The effect of using motion graphic video on the learning process can be seen in the indicators of learning interest, responsiveness, creativity, student enthusiasm, student activity, visual activity, speaking activity, listening activity, mental activity and emotional activity of students. In addition, it was found that there was an increase in student learning outcomes on indicators of cognitive abilities in the form of high-level thinking skills, scientific, critical and creative thinking, an increase in affective abilities in the form of collaborative abilities through the application of motion graphic video media. Motion graphic video media is effectively used as a tool to support science learning in junior high schools in Indonesia.